The challenge of safe anesthesia in developing countries: defining the problems in a medical center in Cambodia - Kun-ming Tao; Sann Sokha; Hong-bin Yuan (BMC, 2020)
Abstract Background The International Standards for a Safe Practice of Anesthesia (ISSPA) were developed on behalf of the World Federation of Societies of Anaesthesiologists and the World Health Organization. It has been recommend as an assessment tool that allows anesthetic providers in developing countries to assess their compliance and needs. This study was performed to describe the anesthesia service in one main public hospital during an 8-month medical mission in Cambodia and evaluate its anesthetic safety issues according to the ISSPA. Methods We conduct a retrospective study involving 1953 patients at the Preah Ket Mealea hospital. Patient demographics, anesthetic techniques, and complications were reviewed according to the registers of the anesthetic services and questionnaires. The inadequacies in personnel, facilities, equipment, medications, and conduct of anesthesia drugs were recorded using a checklist based on the ISSPA. Results A total of 1792 patients received general and regional anesthesia in the operating room, while 161 patients receiving sedation for gastroscopy. The patients' mean age was 45.0 ± 16.6 years (range, 17-87 years). The three most common surgical procedures were abdominal (52.0%; confidence interval [CI], 49.3-54.7), orthopedic (27.6%; CI, 25.2-29.9), and urological surgery (14.7%; CI, 12.8-16.6). General anesthesia, spinal anesthesia, and brachial plexus block were performed in 54.3% (CI, 51.7-56.8), 28.2% (CI, 25.9-30.5), and 9.4% (CI, 7.9-10.9) of patients, respectively. One death occurred. Twenty-six items related to professional aspects, monitoring, and conduct of anesthesia did not meet the ISSPA-recommended standards. A lack of commonly used drugs and monitoring equipment was noted, posing major threats to the safety of anesthesia practice, especially in emergency situations. Conclusions This study adds to the scarce literature on anesthesia practice in low- and middle-income countries such as Cambodia. Future medical assistance should help to strengthen these countries' inadequacies, allowing for the adoption of international standards for the safe practice of anesthesia.